2009
DOI: 10.4049/jimmunol.0803441
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Two Latent Membrane Protein 1 MHC Class I Epitopes Requires Tripeptidyl Peptidase II Involvement

Abstract: The EBV Ag latent membrane protein 1 (LMP1) has been described as a potential target for T cell immunotherapy in EBV-related malignancies. However, only a few CD8+ T cell epitopes are known, and the benefit of LMP1-specific T cell immunotherapy has not yet been proven. In this work, we studied the processing of the two LMP1 HLA-A02-restricted epitopes, YLLEMLRWL and YLQQNWWTL. We found that target cells endogenously expressing the native LMP1 are not recognized by CTLs specific for these epitopes because the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 49 publications
0
17
1
Order By: Relevance
“…Our results indicate that similar to LAP, TPPII also negatively affects pp65 [495][496][497][498][499][500][501][502][503] epitope generation as demonstrated by enhanced pp65 epitope presentation after TPPII knockdown. In contrast, previous observations by Diekmann et al (30) revealed no effect of TPPII on pp65 processing in EBV-transformed B LCLs. An explanation for the observed discrepancy might be the analysis of different cell lines since LCLs primarily contain immunoproteasomes, thereby providing enhanced amounts of proteasomal cleavage products that may compensate for the negative effects of TPPII (see also Fig.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Our results indicate that similar to LAP, TPPII also negatively affects pp65 [495][496][497][498][499][500][501][502][503] epitope generation as demonstrated by enhanced pp65 epitope presentation after TPPII knockdown. In contrast, previous observations by Diekmann et al (30) revealed no effect of TPPII on pp65 processing in EBV-transformed B LCLs. An explanation for the observed discrepancy might be the analysis of different cell lines since LCLs primarily contain immunoproteasomes, thereby providing enhanced amounts of proteasomal cleavage products that may compensate for the negative effects of TPPII (see also Fig.…”
Section: Discussioncontrasting
confidence: 54%
“…1). Overall, the role of TPPII in Ag processing is discussed controversially, indicating limitation of the peptide pool on the one hand (31) and epitope enhancing effects on the other hand (30,(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…24 In brief, 5 ϫ 10 5 partially matched LCLs pulsed with 0.5 g/mL of the AdV hexon protein peptide pool, 0.5 g/mL of the EBV LMP2 peptide pool, or mismatched or CMV pp65-transduced LCLs were used as target cells and pulsed with 100 Ci Na 2 …”
Section: Cytotoxicity Assaymentioning
confidence: 99%
“…19 In the latency period following primary EBV infection, these proteins are exposed to the immune system initiating a T-cell-based immune response later having a crucial role in immunosurveillance of the virus. Many of these cytotoxic T-cell responses target EBNA-3 protein 16 or LMP-2 protein 20 representing potential targets for cellular-based therapies. A key feature of EBV is its potency to induce malignancy in infected B cells.…”
Section: Introductionmentioning
confidence: 99%